Dissecting immunophenotypic diversity in multiple myeloma via mass cytometry: a call for harmonized gating strategies - Singer, Mahmoud; Moloudizargari, Milad; Sanchez, James; Pichiorri, Flavia (Frontiers in Immunology, 2025)
Plasma cell disorders present challenges in phenotypic determination, as they range from monoclonality of plasma cells to multiple myeloma and plasma cell leukemia. According to World Health Organization guidelines, no single aberrant marker is recognized to be uniquely linked to multiple myeloma. The absence of a preset marker panel proven to account for multiple myeloma diversity causes difficulties in diagnosis and clinical research; therefore, the need to create a well-defined panel is urgently needed. For this manuscript, we reviewed the literature on the phenotypic and immunological features that lead to incomplete information and problems in immunophenotyping. We offer proposed solutions for identifying the suitable markers and technology to fill this gap, by using a well-defined gating strategy in a high-dimensional mass cytometry (CyTOF) panel and by next-generation flow cytometry. We analyze pitfalls, starting with sample preparation, selection of the marker panel, gating strategy, cleaning up events, quality control, troubleshooting and validation, and finally, analysis of data. We advance a comprehensive protocol that allows for a detailed analysis of the immunophenotype of myeloma cells. By identifying aberrant markers in the panel, we may be able to facilitate diagnosis and prognosis, ultimately influencing the choice of therapeutic regimens and patients’ overall survival.